Students' Perceptions On The Use Of Animation Movies In English Language Learning - Nadya Khairuna; Siti Ismahani (Eduvest - Journal of Universal Studies, 2024)
This study aims to investigate students' perceptions of using animation movies as a tool for learning English and assess the effectiveness of this approach in improving students' language skills and motivation. The research involved pretest-posttest analysis and a student perception survey. The results show a significant improvement in students' English language skills after using animation movies, supported by positive perceptions from students. The findings suggest that integrating animation movies into English language teaching can enhance students' learning experience and motivation, aligning with previous research on the topic.